Protein kinase R, IκB kinase-β and NF-κB are required for human rhinovirus induced pro-inflammatory cytokine production in bronchial epithelial cells - Edwards, Michael R.; Hewson, Christopher A.; Laza-Stanca, Vasile; Lau, Hoy-Tsun H.; Mukaida, Naofumi; Hershenson, Marc B.; Johnston, Sebastian L. (Molecular immunology, 2007)
Rhinovirus infections cause the majority of acute exacerbations of airway diseases such as asthma and chronic obstructive pulmonary disease, with increased pro-inflammatory cytokine production by infected bronchial epithelial cells contributing to disease pathogenesis. Theses diseases are a huge cause of morbidity worldwide, and contribute a major economic burden to healthcare costs. Current steroid based treatments are only partially efficient at controlling virus induced inflammation, which remains an unmet therapeutic goal. Although NF-κB has been implicated, the precise mechanisms of rhinovirus induction of pro-inflammatory gene expression in bronchial epithelial cells are unclear. We hypothesised that rhinovirus replication and generation of dsRNA was an important process of pro-inflammatory cytokine induction. Using pharmalogical (2-aminopurine and a new small molecule inhibitor) and genetic inhibition of the dsRNA binding kinase protein kinase R, striking inhibition of dsRNA (polyrIC) and rhinovirus induced CCL5, CXCL8 and IL-6 protein was observed. Using confocal microscopy, rhinovirus induced protein kinase R phosphorylation co-located with NF-κB p65 nuclear translocation. Focusing on CXCL8, both rhinovirus infection and dsRNA treatment required IκB kinase-β for induction of CXCL8. Analysis of cis-acting sites in the CXCL8 promoter revealed that both rhinovirus infection and dsRNA treatment upregulated CXCL8 promoter activation via NF-κB and NF-IL6 binding sites. Together, the results demonstrate the importance of dsRNA in induction of pro-inflammatory cytokines by rhinoviruses, and suggest that protein kinase R is involved in NF-κB mediated gene transcription of pro-inflammatory cytokines via IκB kinase-β. These molecules regulating rhinovirus induction of inflammation represent therapeutic targets.